Kohler’s Learning Theory and Its Implications in Modern Learning - Wahyu Garjita, Athaya; Karisma, Sesilya; Ayu Hermawan, Dewi (Department of Educational Technology, Postgraduate Program, State University of Makassar, 2025)
This research examines Köhler’s insight learning theory and its implications for modern learning practices. Using a literature review method, relevant books and peer-reviewed journal articles on Gestalt psychology, insight learning, and contemporary education were systematically analyzed. The findings indicate that insight learning emphasizes holistic understanding and cognitive restructuring rather than rote repetition or stimulus–response associations. When applied to modern learning contexts, Köhler’s theory supports the development of critical thinking and problem-solving skills by encouraging learners to understand relationships among concepts and actively construct meaning. This study concludes that insight learning theory remains relevant for modern education, particularly in designing student-centered learning environments that foster deep conceptual understanding and adaptive problem-solving abilities.